2017
DOI: 10.1016/j.actbio.2016.11.028
|View full text |Cite
|
Sign up to set email alerts
|

3D scaffold with effective multidrug sequential release against bacteria biofilm

Abstract: The present study is focused in finding an adequate therapeutic solution for the treatment of bone infection based on 3D multifunctional scaffolds, which combines the merits of osseous regeneration and local multidrug delivery. These 3D multidrug scaffolds, containing rifampin, levofloxacin and vancomycin, localized in different compartments to achieve different release kinetics. These 3D multidrug scaffolds displays an early and fast release of rifampin followed by sustained and prolonged release of vancomyci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 67 publications
(62 reference statements)
1
47
0
Order By: Relevance
“…However, our results suggest that in addition to the drug diffusion process throughout the mesoporous matrix, a new component is governing the drug release kinetics. Specifically, this new component refers to the MGHA matrix-Levo interactions, as it has been previously reported for other silica matrix [44,45]. Fig.…”
Section: In Vitro Levofloxacin Release Kineticsmentioning
confidence: 86%
“…However, our results suggest that in addition to the drug diffusion process throughout the mesoporous matrix, a new component is governing the drug release kinetics. Specifically, this new component refers to the MGHA matrix-Levo interactions, as it has been previously reported for other silica matrix [44,45]. Fig.…”
Section: In Vitro Levofloxacin Release Kineticsmentioning
confidence: 86%
“…In both cases, δ is minor than 1, showing that the behavior is different from a first order kinetic. The k values varies from 0.021 to 0.51 h −1 for MSN@LEVO and MSN-DAMO@LEVO, respectively, which could point to strong attractive interactions of the LEVO molecules with the Si-OH groups present in the matrix of pristine MSN, as it has been demonstrated elsewhere [34]. The effectiveness of the different released LEVO doses at several times from both MSNs against E. coli and S. aureus bacterial growth was performed.…”
Section: Levofloxacin Loading and Release Assaysmentioning
confidence: 99%
“…However, advances toward creating TECs for in vivo applications have led to progress in designing biomimetic in vitro models for studying bone biology, disease progression, and drug screening in the bone microenvironment. 3D in vitro bone models have been proposed to aid in bridging the gap between 2D culture and animal models for diseases and medical conditions such as osteomyelitis [33], bone fracture healing [34, 35], and, as will be discussed in this review, tumor metastases. In designing such TECs, studies investigating properties of the constructs indicated that characteristics including rigidity [32, 36], pore size [37, 38], pore shape [39], and curvature [40] all affect cell behavior.…”
Section: D Bone Modelsmentioning
confidence: 99%